DIAGNOSIS AND SURGICAL MANAGEMENT OF INCARCERATED OR STRANGULATED HERNIAS (CIPEEX, 2025)
Introduction. Incarcerated and strangulated hernias are severe surgical emergencies frequently encountered by general and critical care surgeons. Immediate recognition is essential to prevent complications such as necrosis of abdominal organs and to reduce associated mortality. Although much of the literature addresses elective hernia repair, there is a growing need for evidence-based guidelines for urgent management. Objective. To analyze the main aspects of clinical and radiological diagnosis and to discuss current surgical management strategies for incarcerated or strangulated hernias, highlighting challenges, therapeutic options, and outcomes. Methods. A narrative literature review was conducted through searches in PubMed and the Virtual Health Library (BVS). Controlled DeCS/MeSH descriptors were used, including Emergency Service, General Surgery, and Hernia. Articles published from 2020 onward, in English, addressing the diagnosis and surgical management of incarcerated or strangulated hernias were included. Reviews, clinical trials, and relevant case series were selected after initial screening. Results. Laparoscopic repair demonstrated outcomes comparable to open repair in terms of complications and recurrence but was associated with less residual pain, improved long-term quality of life, and shorter hospital stay. Risk factors for strangulation and mortality included higher ASA scores, signs of acute abdomen, delayed hospital admission, and laboratory abnormalities such as elevated lactate, procalcitonin, and creatinine. Early intervention (< 6 hours from symptom onset) significantly reduced the need for bowel resection. Mesh repair was associated with lower recurrence, though with variable results regarding surgical site infection. Conclusion. Early diagnosis of incarcerated or strangulated hernias, combined with timely surgical intervention, is crucial to reduce severe complications and mortality. Clinical and radiological evaluation guides decision-making, while the choice between open and laparoscopic approaches should consider organ viability and contamination risk. Despite advances, controversies remain regarding mesh use and laparoscopic approaches in emergency settings, reinforcing the need for evidence-based protocols to optimize surgical outcomes.
Keywords: Emergency Service; General Surgery; Hernia